Analysis of Gender-based Differences in Surgery Faculty Compensation, Promotion, and Retention: Establishing Equity - Hoops, Heather E; Brasel, Karen J; Dewey, Elizabeth; Rodgers, Sally; Merrill, Jenny; Hunter, John G; Azarow, Kenneth S (Annals of surgery, 2018)
The objectives of this study were to evaluate gender-based differences in faculty salaries before and after implementation of a university-wide objective compensation plan, Faculty First (FF), in alignment with Association of American Medical Colleges regional median salary (AAMC-WRMS). Gender-based differences in promotion and retention were also assessed. Previous studies demonstrate that female faculty within surgery are compensated less than male counterparts are and have decreased representation in higher academic ranks and leadership positions. At a single institution, surgery faculty salaries and work relative value units (wRVUs) were reviewed from 2009 to 2017, and time to promotion and retention were reviewed from 1998 to 2007. In 2015, FF supplanted specialty-specific compensation plans. Salaries and wRVUs relative to AAMC-WRMS, time to promotion, and retention were compared between genders. Female faculty (N = 24) were compensated significantly less than males were (N = 62) before FF (P = 0.004). Female faculty compensation significantly increased after FF (P < 0.001). After FF, female and male faculty compensation was similar (P = 0.32). Average time to promotion for female (N = 29) and male faculty (N = 82) was similar for promotion to associate professor (P = 0.49) and to full professor (P = 0.37). Promotion was associated with significantly higher retention for both genders (P < 0.001). The median time of departure was similar between female and male faculty (P = 0.73). A university-wide objective compensation plan increased faculty salaries to the AAMC western region median, allowing correction of gender-based salary inequity. Time to promotion and retention was similar between female and male faculty.